Gambaran Asupan Gizi Dan Aktivitas Fisik Pada Pekerja Kantoran Overweight Di Karawang - Anggun Agustaria Elkana; Anggun Dwi Sulistiani; Syarafina Sabila; Sabrina Sabrina (Jurnal Gizi dan Kuliner, 2023)
Overweight is excess body weight including muscle, bone, fat, and water. a higher incidence of overweight may lead to another epidemic such as obesity. Intake of incoming and outgoing energy must be balanced because it can cause non-communicable diseases such as the risk of cardiovascular disease, type 2 diabetes mellitus, to disorders of the musculoskeletal system. This study aimed to describe nutritional intake and physical activity in office workers in Karawang. This study involved 3 office workers, 2 women, and 1 man. The data collected is primary data consistingof interview results and food recall 1 x 24 hours. Based on the results of this study, it can be concluded that eating patterns are related to the occurrence of being overweight. The average respondent has a bad diet. Thus, a poor diet will have an impact on increasing body mass index (overweight), where food intake is not sufficient to meet the needs of women of childbearing age and are at risk of experiencing other disorders or diseases caused by excess nutrition. Conversely, intake that is less than the body's needs can cause the body to become thin and susceptible to disease. So a good diet (nutritional intake) is in accordance with the needs of the body based on age group, gender, and daily activities. Keywords: Overweight, Intake, Worker